Role of DNA gyrase subunits in synthesis of bacteriophage phi X174 viral DNA. - Hamatake, R K (1981)
The role of Escherichia coli DNA gyrase subunit A and subunit B during phi X174 viral DNA synthesis was investigated. Addition of nalidixic acid (an inhibitor of gyrase subunit A) and novobiocin (an inhibitor of gyrase subunit B) to an in vitro system capable of synthesizing phi X174 viral DNA inhibited DNA synthesis. The inhibition caused by novobiocin, however, was not due specifically to an inhibition of gyrase subunit B because DNA synthesis in an in vitro system composed of an extract containing novobiocin-resistant gyrase subunit B was also inhibited by novobiocin. The requirement for gyrase subunit A and the dispensability of gyrase subunit B during viral strand synthesis was confirmed in vivo by examining phi X174 viral DNA synthesis in host bacteria containing temperature-sensitive gyrase subunits.